2018
DOI: 10.1080/19420862.2018.1521130
|View full text |Cite
|
Sign up to set email alerts
|

Non-neutralizing antibodies increase endogenous circulating Ang1 levels

Abstract: Ang1 is a soluble ligand to receptor Tie2, and increasing the circulating Ang1 level may improve vascular stabilization under certain disease conditions. Here, we found that the circulating Ang1 level was significantly increased in cynomolgus monkeys treated with non-neutralizing anti-Ang1 antibodies. Improving the antibodies’ pharmacokinetic properties by IgG Fc mutations further increased the circulating Ang1 level. However, the mutations decreased the thermal stability of the molecules, which may limit thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Finally, the present study tested a recently described and novel biotherapeutic modality to increase endogenous ANGPT1 protein levels using a non-neutralizing anti-ANGPT1 antibody, referred to as O010, that binds within the coiled-coil domain of ANGPT1 (a site independent of the receptor binding domain) and reduces the clearance, resulting in increased circulating concentrations of ANGPT1. It was previously shown that the O010 antibody does not interfere with ANGPT1 binding to TIE2, nor does it reduce pAKT signaling in a cell line (Zheng et al, 2018). Furthermore, this antibody significantly increases circulating ANGPT1 levels in healthy cynomolgus monkeys (Zheng et al, 2018) consistent with the targeted mechanism-of-action.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Finally, the present study tested a recently described and novel biotherapeutic modality to increase endogenous ANGPT1 protein levels using a non-neutralizing anti-ANGPT1 antibody, referred to as O010, that binds within the coiled-coil domain of ANGPT1 (a site independent of the receptor binding domain) and reduces the clearance, resulting in increased circulating concentrations of ANGPT1. It was previously shown that the O010 antibody does not interfere with ANGPT1 binding to TIE2, nor does it reduce pAKT signaling in a cell line (Zheng et al, 2018). Furthermore, this antibody significantly increases circulating ANGPT1 levels in healthy cynomolgus monkeys (Zheng et al, 2018) consistent with the targeted mechanism-of-action.…”
Section: Discussionmentioning
confidence: 67%
“…It was previously shown that the O010 antibody does not interfere with ANGPT1 binding to TIE2, nor does it reduce pAKT signaling in a cell line (Zheng et al, 2018). Furthermore, this antibody significantly increases circulating ANGPT1 levels in healthy cynomolgus monkeys (Zheng et al, 2018) consistent with the targeted mechanism-of-action. The present study also demonstrated an increase in circulating ANGPT1 with O010 in db/db UNx mice, however the molecule failed to reduce renal injury endpoints including no effect on albuminuria or histopathology scores, including the incidence of glomerulosclerosis and interstitial lesions.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations